Synthesis of cyclobutane-fused oxygen-containing tricyclic framework via thermally promoted intramolecular cycloaddition of cyclohexadienone-tethered allenes. Issue 23 (24th February 2020) - Zhai, Shengxian; Qiu, Shuxian; Chen, Lunjian; Niu, Yongsheng; Yu, Youzhu; Yang, Bo; Zhang, Beining; Han, Chuchu; Yang, Liguo; Zhai, Hongbin
Abstract : A unique approach for the thermally-promoted cycloaddition of cyclohexadienone-tethered allenes to form versatile cyclobutane-fused oxygen-containing tricyclic framework is reported. Abstract : We have developed a unique approach for the thermally promoted cycloaddition of cyclohexadienone-tethered allenes to form a versatile cyclobutane-fused oxygen-containing tricyclic framework in an environmentally friendly and atomic economic fashion with high regioselectivity. The reaction encompasses a broad substrate scope and functional group tolerance of cyclohexadienone moieties. Moreover, the cycloaddition was also applicable to the late-stage functionalization of pharmaceutically relevant compounds.